Allergy and cancer: Analysis of the American Cancer Society Cancer Prevention Study II prospective cohort - Turner, Michelle Catherine (University of Ottawa (Canada), 2004)
The presence of allergy may reduce cancer risk. Literature searches identified 142 epidemiological studies on this association. Data from the American Cancer Society Cancer Prevention Study-II cohort were used to explore the relationship between self-reported asthma and/or hay fever and cancer mortality in 508 318 men and 483 079 women who were cancer-free at baseline. During 18 years of follow-up from 1982--2000, there were 44 524 cancer deaths in men and 36 567 in women. Cox proportional hazards models were used to obtain adjusted relative risks for overall cancer mortality and for cancer mortality at 12 sites. There was approximately a 10% reduction in overall cancer mortality among people with asthma and hay fever. Asthma and/or hay fever were also associated with a reduced risk of cancer at a number of other sites, and some of the associations were modified by gender and smoking status.
Keywords: Health Sciences, Public Health.; Health Sciences, Oncology.